2014
DOI: 10.1155/2014/131452
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Cecal Diverticulitis: An Unusual Cause of Acute Right Iliac Fossa Pain—A Case Report and Review of the Literature

Abstract: Solitary cecal diverticulitis is a rare cause of acute abdominal pain in the Western world. Its clinical presentation, in most cases, mimics acute appendicitis. A 38-year-old Caucasian man presented with acute abdomen and clinical signs of acute appendicitis. Laparotomy was performed and revealed an inflammatory, solitary diverticulum of the cecum. A typical appendectomy was performed and a catheter was inserted for draining percutaneously the inflamed diverticulum of the cecum. The patient had an uneventful r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…If a solitary cecal diverticulum is clearly identified at the time of surgery, some authors advocate no intervention, while others recommend a simple diverticulectomy, or at least invagination of the diverticulum combined with appendectomy. [12] In the presence of marked inflammatory changes or complications, such as free perforation, torsion, or localized abscess formation, ileocecal resection or right hemicolectomy should be considered. [13] Yang et al, [14] reported that if perioperative malignancy was suspected, right hemicolectomy is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…If a solitary cecal diverticulum is clearly identified at the time of surgery, some authors advocate no intervention, while others recommend a simple diverticulectomy, or at least invagination of the diverticulum combined with appendectomy. [12] In the presence of marked inflammatory changes or complications, such as free perforation, torsion, or localized abscess formation, ileocecal resection or right hemicolectomy should be considered. [13] Yang et al, [14] reported that if perioperative malignancy was suspected, right hemicolectomy is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CD is still controversial, varying from conservative therapy to aggressive surgery. [6,15,16] There is no consensus among surgeons as to the best option. There are studies recommending conservative medical treatment or only diverticulectomy, if technically possible, for the treatment of CD cases, and these studies havereported that excisional treatment prevent the relapse of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies recommending conservative medical treatment or only diverticulectomy, if technically possible, for the treatment of CD cases, and these studies havereported that excisional treatment prevent the relapse of the symptoms. [15] In the presence of excess inflammatory changes, multiple diverticulum and caecal phlegmon or if cancer cannot be excluded; aggressive resection like right hemicolectomy should be considered. Because, in these patients, surgical treatment can be applied safely without any major complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of cecal diverticulitis is still controversial, varying from conservative therapy to aggressive surgery, such as right hemicolectomy [9]. Conservative management of cecal diverticulitis may be an effective treatment modality in cases diagnosed with imaging techniques.…”
mentioning
confidence: 99%